A STUDY OF AEGYPTIANELLA SPP IN SOME SPECIES OF BIRDS IN MOSUL CITY-IRAQ - E.G.Suleiman (Basrah Journal of Veterinary Research)
During this study examination of 205 blood samples collected from four species of birds , chickens(50), ducks(75), turkeys(30), and pigeon(50) in different regions of Mosul city for the detection of Aegyptianella spp. The total percentage of infection was 28.29% and infection was (33.33%), (30%), (26.66%), and (20%) in ducks ,pigeons, turkeys and chickens respectively . An Anaplasma –like organism form ,rounded and piriform shaped with varying sizes 0.83-4.15μ . Parasitemia in chickens, pigeons, turkeys, and ducks respectively were1.7%, 2.5%, 2.6%, 2.8%.